Targeted omics analyses, and metabolic enzyme activity assays demonstrate maintenance of key mucociliary characteristics in long term cultures of reconstituted human airway epithelia. Issue 5 (August 2015) - Baxter, Andrew; Thain, Simon; Banerjee, Anisha; Haswell, Linsey; Parmar, Aleesha; Phillips, Gary; Minet, Emmanuel
Highlights Characterization of long term MucilAir™ cultures to evaluate suitability for repeat-dose testing of inhaled chemicals. Airway surface liquid marker proteins are secreted in long term MucilAir™ cultures. Expression of genes coding for xenobiotics metabolizing enzymes is similar between MucilAir™ and normal lung. Activity of CYPs involved in the bioactivation of inhaled toxicants is present and maintained in long term MucilAir™ cultures.